The Vulnerability Assessment ofProcess Plant in Malays - Mamujalean, Mohd Hafez (Universiti Teknologi PETRONAS, 2009)
This report presents aresearch ofa prototype methodology to assess the security of chemical facilities within the Malaysia. The Vulnerability Assessment (VA) do identifies andassesses potential security threats, risks, and vulnerabilities and guides the chemical facility industry in making security improvements. The National Institute of Justice developed the Vulnerability Assessment Methodology (VAM) in collaboration with the Department ofEnergy's Sandia National Laboratories. Sandia National Laboratories employees are recognized experts in security andcounterterrorism andhaveextensive experience inthe protection ofnuclear weapons and radiological materials for the process plant The objectives of theproject areto study thevulnerability assessment framework and dothe implementation by doing a case study inPETRONAS operation unit. Inthis project, the Vulnerability Assessment Methodology (VAM) by Sandia National Laboratories is used asguidance to implement vulnerability assessment in PETRONAS plantprocess. The challenge in this project is dothecase study in one of theOPU in which involved collecting theplantdata process